Реакция мозга человека на ольфакторную стимуляцию - Воропай, В. С. (Кременчук: КрНУ, 2017, 2017)
There are the main information about the olfactory disorders, methods of their diagnosis, in particular – olfactometry. A brief analysis of the advantages and disadvantages of existing methods is given. The possibility of applying electroencephalography for the modernization of the existing method. Characteristics of the main changes in the electroencephalogram when a person inhales odors.
Keywords: обоняние, риноманометрия,стимуляция, ольфакторный, реакция, мозг